Prudencia del resultado bajo las normas internacionales de contabilidad: un estudio comparado en Europa - Rueda Torres, Juan Antonio (Cuadernos de Estudios Empresariales, 2006)
Financial reporting reliability (and utility) requires conservatism measure of earnings, in terms of higher timeliness in the recognition of economic losses (bad news) relative to economic profits (good news). For a sample of European firms over the period 1994-2003, we measure earnings conservatism by using stock returns as a proxy of economic income, and by testing the persistence of changes in accounting earnings. We find that timely recognition degree of economic losses in accounting earnings by firms complying with International Accounting Standards (IAS) is significant higher to the earnings timeliness under Spanish accounting standards. Nevertheless, conservatism of earnings reported according to IAS is weakly higher than earnings conservatism under UK accounting standards. Our results suggest that incentives faced by managers and auditors from European countries in issuing financial statements seem to have a limited effect on quality of the IAS themselves.